Nanotechnology in Cancer Treatment: Innovative Approaches to Overcoming Drug Resistance in Tumors - Eskandar, Kirolos (Indonesian Society for Cancer Chemoprevention, 2024)
Nanotechnology has emerged as a groundbreaking approach in oncology, offering innovative solutions to one of the most significant challenges in cancer treatment: drug resistance. This literature review explores the role of nanotechnology in overcoming multidrug resistance (MDR) in tumors, focusing on the use of nanoparticles for targeted drug delivery, gene therapy, and immunotherapy. By penetrating biological barriers and modulating the tumor microenvironment, nanocarriers enhance the efficacy of anticancer agents while minimizing side effects. Additionally, this review provides a comprehensive analysis of recent clinical trials, offering insights into the real-world effectiveness of nanotechnology-based treatments. Ethical, regulatory challenges, and nanotoxicity are discussed to ensure the safe translation of nanomedicine to clinical practice. The review concludes with future directions in personalized nanomedicine, highlighting nanotechnology’s transformative potential in revolutionizing cancer treatment and improving patient outcomes by addressing the pervasive issue of drug resistance.Keywords: nanotechnology, drug resistance, nanoparticles, targeted drug delivery, cancer therapy.